The Crucial Role of Pharmacists in Dentistry: A Comprehensive Review (Academia Journal of Medicine, 2023)
The field of dentistry goes beyond the skills of  dental professionals alone. Collaborative efforts  among different healthcare providers are crucial  for comprehensive patient care. One such critical  role is played by pharmacists in dentistry.  Pharmacists bring their expertise in medications  and their interactions to ensure the safe and  effective use of drugs prescribed by dentists. In  this article, we will discuss the vital contributions of  pharmacists in dental care and their role in  promoting oral health.
Keywords: Pharmacist; Dentistry; Oral Health